Terjadi Penyempitan Ruang Demokratis Di Indonesia yang Makin Menguat Gejalanya di Masa Pandemi - Diah Sara; Rini Ratnasari Lumbantoruan; Novia Fitri; Rangga perdana; Wahjoe Pangestoeti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Indonesia has undergone a transition towards a democratic system since the 1998 reformasi, but the quality of its democracy has significantly declined since 2013. Civil liberties have decreased, accompanied by an increase in persecution cases against minority groups and the use of the Information and Electronic Transactions Law (ITE) to restrict freedom of speech. The COVID-19 pandemic has posed additional challenges with emergency policies that limit human rights, such as freedom of assembly and movement, as well as the adoption of controversial laws that have sparked protests. Political elites play a key role in upholding democracy and civil liberties. Strengthening democracy in the future requires better political transparency, strong protection of human rights, and active civil society participation in monitoring the political process. With these steps, Indonesia can continue its journey towards a more inclusive, transparent, and resilient political system in the future.